Differential lung gene expression changes in C57BL/6 and DBA/2 mice carrying an identical functional Mx1 gene reveals crucial differences in the host response - Silke Bergmann; Linda Brunotte; Klaus Schughart (BMC Genomic Data, 2024)
Abstract Background Influenza virus infections represent a major global health problem. The dynamin-like GTPase MX1 is an interferon-dependent antiviral host protein that confers resistance to influenza virus infections. Infection models in mice are an important experimental system to understand the host response and susceptibility to developing severe disease following influenza infections. However, almost all laboratory mouse strains carry a non-functional Mx1 gene whereas humans have a functional MX1 gene. Most studies in mice have been performed with strains carrying a non-functional Mx1 gene. It is therefore very important to investigate the host response in mouse strains with a functional Mx1 gene. Results Here, we analyzed the host response to influenza virus infections in two congenic mouse strains carrying the functional Mx1 gene from the A2G strain. B6.A2G-Mx1 r/r (B6-Mx1 r/r ) mice are highly resistant to influenza A virus (IAV) H1N1 infections. On the other hand, D2(B6).A2G-Mx1 r/r (D2-Mx1 r/r ) mice, although carrying a functional Mx1 gene, were highly susceptible, exhibited rapid weight loss, and died. We performed gene expression analysis using RNAseq from infected lungs at days 3 and 5 post-infection (p.i.) of both mouse strains to identify genes and pathways that were differentially expressed between the two mouse strains. The susceptible D2-Mx1 r/r mice showed a high viral replication already at day 3 p.i. and exhibited a much higher number of differentially expressed genes (DEGs) and many DEGs had elevated expression levels compared to B6-Mx1 r/r mice. On the other hand, some DEGs were specifically up-regulated only in B6-Mx1 r/r mice at day 3 p.i., many of which were related to host immune response functions. Conclusions From these results, we conclude that at early times of infection, D2-Mx1 r/r mice showed a very high and rapid replication of the virus, which resulted in lung damage and a hyperinflammatory response leading to death. We hypothesize that the activation of certain immune response genes was missing and that others, especially Mx1, were expressed at a time in D2-Mx1 r/r mice when the virus had already massively spread in the lung and were thus not able anymore to protect them from severe disease. Our study represents an important addition to previously published studies in mouse models and contributes to a better understanding of the molecular pathways and genes that protect against severe influenza disease.